The Second Language Influence On Using Translation In Content -based Instruction Classroom: The Case Of French Language For Algerian Teachers Teaching Content In English - Aissa Hanifi; Naimi Amara; Khawla Ladjel (The Journal of Studies in Language, Culture and Society, 2025)
The use of translation in EFL classes has long been a source of discussion among language instructors and industry experts. While some contend that using L1 in an EFL classroom will impede students' ability to learn, others maintain that translation can aid in language acquisition if it is connected to a genuine communicative goal.The situation may look more problematic in a learning context where French and English swap roles and compete to be a essential language of teaching such as the Algerian learning context . In order to illustrate content teachers' opinions about the role of the second language in translating challenging course concepts, an online survey was sent to 32 university teachers. The results indicated that teachers feel obligated to translate challenging concepts into Arabic or French because of students' poor English proficiency. The purpose of the current study is to shed light on the impact of French as a second language on Algerian teachers who aim to or currently instruct content in English across the different disciplines. . Furthermore, the majority of teachers did not state categorically which language—French or Arabic—they would use to interpret complex phrases in the CBI course because this could depend on the students' proficiency in both languages, their real needs, and the course objectives.